2011
DOI: 10.1111/j.2041-210x.2011.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving prediction and management of range expansions by combining analytical and individual‐based modelling approaches

Abstract: Summary1. Improving the understanding, prediction and management of range expansions is a key challenge for ecology. Over recent years, there has been a rapid increase in modelling effort focussed on range expansions and a shift from predominantly theoretical developments towards application. This is especially the case in the field of invasion biology and also in relation to reintroductions and species' responses to climate change. 2. While earlier models were exclusively analytical, individual-based models (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 42 publications
3
46
0
Order By: Relevance
“…[20] have also highlighted the value of using both deterministic and stochastic modelling approaches when predicting invasion speeds. They found that though both models produced similar trends, their analytical model predicted significantly higher speeds than their stochastic IBM [20].…”
Section: Introductionmentioning
confidence: 99%
“…[20] have also highlighted the value of using both deterministic and stochastic modelling approaches when predicting invasion speeds. They found that though both models produced similar trends, their analytical model predicted significantly higher speeds than their stochastic IBM [20].…”
Section: Introductionmentioning
confidence: 99%
“…Travis et al. (2011) have argued have argued for, and explored the advantages of, using both analytical IDEs and individual-based approaches in the context of climate driven range expansions.…”
Section: Introductionmentioning
confidence: 99%
“…While it may be possible to develop control measures against plant pests once they are widespread, it is much more effective in terms of time, cost and ultimate success to take action before a pest becomes widespread (Wadsworth et al, 2000; Johnson and Turner, 2010; Kapustka, 2010;Travis et al, 2011). Therefore, risk assessment at an early stage in plant pest invasion forms a valuable weapon against their damaging impacts.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…As globalisation of trade in commodities able to harbour plant pests continues it seems inevitable that many more novel pest introductions to Europe will occur in the future (Meyerson and Mooney, 2007; Hulme, 2009). Furthermore, changing climatic and other environmental conditions may lead to a greater propensity for introduced pests to establish, spread and cause impact than has been observed historically (Walther et al, 2009).While it may be possible to develop control measures against plant pests once they are widespread, it is much more effective in terms of time, cost and ultimate success to take action before a pest becomes widespread (Wadsworth et al, 2000; Johnson and Turner, 2010; Kapustka, 2010;Travis et al, 2011). Therefore, risk assessment at an early stage in plant pest invasion forms a valuable weapon against their damaging impacts.…”
mentioning
confidence: 99%